Preparation And Properties Of Rubber Seed Kernel Powder/Recycled Polystyrene Composites - Hawari, Akmal Afham (2014)

(untitled)
Recycled polystyrene (RPS)/rubber seed kernel powder (RSKP) composites at 0, 1, 3, 5, and 10 wt% of RSKP were prepared in an internal mixer at 180°C with 60 rpm of rotor speed for 8 minutes. Processing torque, tensile strength, elongation at break, Young’s modulus and impact strength decreased with higher RSKP loadings, but water absorption increased. In comparison to virgin polystyrene (VPS)/RSKP, RPS/RSKP composites had lower processing torque, tensile strength, elongation at break, impact strength and water absorption. Maleic anhydride (MAH) incorporation into RPS/RSKP composites showed higher tensile strength, elongation at break, Young’s modulus and impact strength as compared to RPS/RSKP composites. The presence of MAH increased the impact strength at 1, 3, and 5 wt% of RSKP loadings. Modifying of RSKP filler with natural rubber latex improved tensile strength, elongation at break and impact strength for RPS/RSKP composites.